A catalyst for dehydrogenating cyclohexanol to produce cyclohexanone, and its preparation method and application

By using a catalyst composed of CuO, ZnO, Cr2O3, ZrO2 and graphite, the problem of difficulty in taking into account both the conversion rate and selectivity in the cyclohexanol dehydrogenation reaction in the prior art is solved, and high activity and high selection at higher temperatures are achieved simplifies the preparation process.

CN114797882BActive Publication Date: 2025-02-21QUZHOU JUHUA POLYAMIDE FIBER LLC +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210338239.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-01
Publication Date
2025-02-21
Estimated Expiration
2042-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high conversion and high selectivity in the cyclohexanol dehydrogenation reaction, especially in the case of a decrease in the stability and selectivity of the catalyst at higher temperatures.

Method used

The catalyst composed of CuO, ZnO, Cr2O3, ZrO2 and graphite is prepared by co-precipitation, drying, calcining and graphite addition, and the formulation and preparation parameters of the catalyst are optimized to improve the activity and selectivity of the catalyst.

Benefits of technology

At higher gas-phase dehydrogenation temperature, the cyclohexanol conversion rate of the catalyst reached more than 72.1%, and the cyclohexanone selectivity reached more than 99.3%, which significantly improved the activity and selectivity of the catalyst and simplified the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003577464270000051
    Figure BDA0003577464270000051
  • Figure BDA0003577464270000061
    Figure BDA0003577464270000061
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing cyclohexanone by dehydrogenation of cyclohexanol. The catalyst is composed of an active component and graphite accounting for 0.1-0.3% of the mass of the active component. The active component is composed of 20-45wt% of CuO, 25-40wt% of ZnO, 14-30wt% of Cr2O3, and 10-20% of ZrO2 by mass percentage. The invention also discloses a preparation method of the catalyst and application of the catalyst in preparing cyclohexanone. The catalyst of the invention is used for preparing cyclohexanone by dehydrogenation of cyclohexanol and has good activity and selectivity at a relatively high gas phase dehydrogenation temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a catalyst for preparing cyclohexanone by dehydrogenating cyclohexanol, and a preparation method and application thereof. Background Art

[0002] Cyclohexanone is an important organic chemical raw material, which is mainly produced by catalytic dehydrogenation of cyclohexanol. At present, dehydrogenation catalysts can be divided into two categories according to the different active components of the catalyst: Zn-based catalysts and Cu-based catalysts. The advantage of Zn-based catalysts is high conversion rate, but the reaction temperature is high, generally at 350-400°C, the selectivity is poor, and the catalyst life is short. The advantage of Cu-based catalysts is good selectivity, but during the use of Cu-based catalysts, the reaction temperature rises to above 280°C, which will accelerate the sintering of copper, reduce the active surface area, and significantly change the carrier structure, so that the activity of the catalyst is significantly reduced and the catalyst stability is poor. At present, based on the characteristics of cyclohexanol dehydrogenation reaction, most studies optimize the dehydrogenation process by improving the catalyst.

[0003] For example, patent CN113070069A discloses a catalyst for dehydrogenating cyclohexanol to produce cyclohexanone, and its preparation method and application. The catalyst is composed of Al 2 O 3 The active components are loaded with CuO, SiO 2 and Cr 2 O 3 , the structural auxiliary agent is La 2 O 3 or CeO 2 The mass content of the active component CuO is 30-45%, and the mass content of the active component SiO 2 The mass content is 10-20%, and the active component Cr 2 O 3 The mass content of the polyol is 10-20%, and the mass content of the structural additive is 2-6%.

[0004] For example, patent CN112387288A discloses a preparation method and application of a medium-temperature cyclohexanol dehydrogenation catalyst. The catalyst uses silicon dioxide as a carrier and carries composite oxides of copper, zinc and calcium as active components and active auxiliary components; the catalyst is prepared by a deposition precipitation method, and is aged, filtered, washed, dried, calcined, and finally pressed into tablets.

[0005] For example, patent CN103861626A discloses a catalyst for dehydrogenating cyclohexanol to cyclohexanone and its application. The catalyst is composed of phosphide of metal iron, cobalt or nickel and tungsten oxide as active components, with Al 2 O 3 、SiO 2Alternatively, porous ceramics are used as carrier materials, and alkali metal or alkaline earth metal oxides are added to modify the catalyst, and the catalyst is prepared by a multi-step impregnation method.

[0006] For example, patent CN103285847A discloses a dehydrogenation catalyst, a preparation method and application thereof, and a method for preparing cyclohexanone by dehydrogenating cyclohexanol. The method comprises: under coprecipitation conditions, a soluble salt of a dehydrogenation active component is contacted with a precipitant capable of precipitating a cation of the soluble salt in water, and then filtered to obtain a solid precipitate, and the solid precipitate is dried or not dried and then roasted; the dehydrogenation active component contains Zn, Ca and Ba, and the molar ratio of Zn, Ca and Ba is 3-1000:5-50:1, and the contact is carried out in the presence of an organic compound containing a functional group hydroxyl.

[0007] The conversion rate and selectivity of cyclohexanol dehydrogenation catalysts prepared by the prior art cannot be optimized at the same time. When dehydrogenating at a relatively low temperature, the conversion rate is low; while when dehydrogenating at a relatively high temperature, the selectivity of cyclohexanone generally decreases, and the catalyst stability needs to be improved. Summary of the invention

[0008] In view of the above deficiencies in the prior art, the object of the present invention is to provide a catalyst for dehydrogenating cyclohexanol to cyclohexanone, and a preparation method and application thereof. The catalyst preparation process of the present invention is simple, and when used for dehydrogenating cyclohexanol to cyclohexanone, it has good activity and selectivity at a higher gas phase dehydrogenation temperature.

[0009] To achieve the above object, the technical solution adopted by the present invention is: a catalyst for dehydrogenating cyclohexanol to cyclohexanone, the catalyst comprising an active component and graphite accounting for 0.1-0.3% of the mass of the active component, and the active component is composed of 20-45wt% (wt%, mass percentage) of CuO, 25-40wt% of ZnO, 14-30wt% of Cr 2 O 3 , 10~20% ZrO 2 .

[0010] The present invention also discloses a method for preparing the catalyst for preparing cyclohexanone by dehydrogenating cyclohexanol, comprising the following steps:

[0011] (1) preparing a mixed aqueous solution of soluble salts of active components according to a molar ratio of copper, zinc, chromium and zirconium of 1.5 to 5:2.5 to 5:1.5 to 5:1;

[0012] (2) reacting the mixed aqueous solution of the soluble salt of the active component obtained in step (1) with an aqueous solution of a precipitant, filtering, and washing to obtain a solid precipitate;

[0013] (3) drying and calcining the solid precipitate to obtain a calcined product;

[0014] (4) adding graphite to the calcined product and then forming the product into sheets to obtain a catalyst for dehydrogenation of cyclohexanol to cyclohexanone.

[0015] Preferably, the soluble salt of the active ingredient is a nitrate.

[0016] Preferably, the precipitating agent is one or more of potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate.

[0017] Preferably, the concentration of the precipitant aqueous solution is 0.5-1.5 mol / L.

[0018] Preferably, the reaction temperature is 30-90° C. and the reaction time is 2-5 h.

[0019] Preferably, the drying temperature is 110-140° C., and the drying time is 5-8 hours.

[0020] Preferably, the calcination temperature is 450-650° C., and the calcination time is 4-10 hours.

[0021] The present invention also discloses the application of the catalyst in the preparation of cyclohexanone. The specific application method is: under the action of the catalyst, cyclohexanol is subjected to a dehydrogenation reaction to prepare cyclohexanone, wherein the temperature of the dehydrogenation reaction is 200-300°C, the pressure is 0.1-0.3MPa, and the cyclohexanol space velocity is 0.8-1.5h -1 .

[0022] Preferably, the catalyst is activated using a mixture of hydrogen and nitrogen before the dehydrogenation reaction, the activation temperature is 200-400° C., the time is 30-50 hours, and the volume concentration of hydrogen in the mixture is 0.1-10%.

[0023] The present invention contacts the soluble salt of the catalyst active component with a precipitant capable of precipitating the cation of the soluble salt in water under coprecipitation conditions, and then filters to obtain a solid precipitate, and then dries and roasts to obtain a catalyst product. The catalyst of the present invention is used for dehydrogenating cyclohexanol to produce cyclohexanone, and has good activity and selectivity at a relatively high gas phase dehydrogenation temperature.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The catalyst has good activity. The present invention optimizes the catalyst formula and preparation parameters, and the active components in the prepared catalyst cooperate with each other, and the catalyst has good activity and selectivity. The catalyst of the present invention is used for dehydrogenating cyclohexanol to produce cyclohexanone. At a relatively high gas phase dehydrogenation temperature, the cyclohexanol conversion rate is above 72.1%, and can reach up to 75.1%; the cyclohexanone selectivity is above 99.3%, and can reach up to 99.6%.

[0026] 2. The preparation process is simple. In the present invention, under co-precipitation conditions, the soluble salt of the catalyst active component is contacted with a precipitant capable of precipitating the cation of the soluble salt in water, and then filtered to obtain a solid precipitate, which is then dried and roasted to obtain a catalyst product. The preparation process is simple to operate and the reaction conditions are mild. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is further described in detail below through examples, but the present invention is not limited to the following examples.

[0028] Example 1

[0029] According to the molar ratio of copper, zinc, chromium and zirconium being 4.7:4.5:4.7:1, 5L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; at a stirring speed of 200rpm and 60°C, 1mol / L of potassium carbonate aqueous solution was added to the mixed aqueous solution for reaction, and the amount of potassium carbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After the reaction was allowed to stand for 2h, the supernatant was analyzed, and no metal ions were detected. The reaction solution was filtered and washed to obtain a precipitate; the obtained precipitate was dried at 120°C for 8h; and then calcined at 450°C for 10h to obtain a calcined product. Based on the mass of the prepared calcined product, the mass content of CuO was 30.7%, the mass content of ZnO was 29.7%, and the mass content of Cr was 2.3%. 2 O 3 The mass content of ZrO is 29.5%, 2 The mass content of the calcined product is 10.1%; finally, 0.15% of the mass of the calcined product is added to the calcined product to form a sheet of graphite to obtain (h) Cylindrical catalyst.

[0030] Example 2

[0031] According to the molar ratio of copper, zinc, chromium and zirconium of 1.7:3.2:1.8:1, 5L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; at a stirring speed of 150rpm and 40°C, 1.2mol / L of sodium carbonate aqueous solution was added to the mixed aqueous solution for reaction, and the amount of sodium carbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After the reaction for 4h, the mixture was allowed to stand for stratification, and the upper clear liquid was analyzed. No metal ions were detected. The reaction solution was filtered and washed to obtain a precipitate; the obtained precipitate was dried at 110°C for 6h; and then calcined at 500°C for 8h to obtain a calcined product. Based on the mass of the prepared calcined product, the mass content of CuO was 20.8%, the mass content of ZnO was 39.6%, and the mass content of Cr was 1.3%. 2 O 3 The mass content of ZrO is 20.8%, 2 The mass content is 18.8%; finally, 0.25% of the mass of the calcined product is added to the calcined product to form a sheet of graphite to obtain (h) Cylindrical catalyst.

[0032] Example 3

[0033] According to the molar ratio of copper, zinc, chromium and zirconium being 3.6:4.9:4.6:1, 5L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; at a stirring speed of 120rpm and 50°C, 0.8mol / L of ammonium carbonate aqueous solution was added to the mixed aqueous solution for reaction, and the amount of ammonium carbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After the reaction for 5h, the mixture was allowed to stand for stratification, and the upper clear liquid was analyzed. No metal ions were detected. The reaction solution was filtered and washed to obtain a precipitate; the obtained precipitate was dried at 120°C for 6h; and then calcined at 650°C for 4h to obtain a calcined product. Based on the mass of the prepared calcined product, the mass content of CuO was 24.6%, the mass content of ZnO was 34.8%, and the mass content of Cr was 24.6%. 2 O 3 The mass content of ZrO is 30%, 2 The mass content of the calcined product is 10.6%; finally, 0.1% of the mass of the calcined product is added to the calcined product and then the calcined product is formed into sheets to obtain (h) Cylindrical catalyst.

[0034] Example 4

[0035] According to the molar ratio of copper, zinc, chromium and zirconium being 4.5:2.5:1.6:1, 5L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; at a stirring speed of 240rpm and 30°C, 1.5mol / L of ammonium bicarbonate aqueous solution was added to the mixed aqueous solution for reaction, and the amount of ammonium bicarbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After the reaction for 5h, the mixture was allowed to stand for stratification, and the upper clear liquid was analyzed. No metal ions were detected. The reaction solution was filtered and washed to obtain a precipitate; the obtained precipitate was dried at 130°C for 5h; and then calcined at 550°C for 8h to obtain a calcined product. Based on the mass of the prepared calcined product, the mass content of CuO was 44.3%, the mass content of ZnO was 25.6%, and the mass content of Cr was 2.6%. 2 O 3 The mass content of ZrO is 14.9%, 2 The mass content is 15.2%; finally, 0.3% of the mass of the calcined product is added to the calcined product to form a sheet of graphite, and the obtained Cylindrical catalyst.

[0036] Example 5

[0037] According to the molar ratio of copper, zinc, chromium and zirconium of 2.7:2.9:2.6:1, 3L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; at a stirring speed of 280rpm and 70°C, 1mol / L of potassium bicarbonate aqueous solution was added to the mixed aqueous solution for reaction, and the amount of potassium bicarbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After the reaction for 3h, the mixture was allowed to stand and the layers were separated. The upper clear liquid was analyzed and no metal ions were detected. The reaction solution was filtered and washed to obtain a precipitate; the obtained precipitate was dried at 130°C for 7h; and then calcined at 600°C for 6h to obtain a calcined product. Based on the mass of the prepared calcined product, the mass content of CuO was 28.1%, the mass content of ZnO was 30.4%, and the mass content of Cr was 1.3%. 2 O 3 The mass content of ZrO is 25.6%, 2 The mass content of the calcined product is 15.9%; finally, 0.2% of the mass of the calcined product is added to the calcined product to form a sheet of graphite to obtain (h) Cylindrical catalyst.

[0038] The catalyst of the present invention is used for the dehydrogenation reaction of cyclohexanol to prepare cyclohexanone:

[0039] The catalysts obtained in Examples 1 to 5 were respectively loaded into fixed bed reactors, and a mixed gas of hydrogen and nitrogen was introduced for activation treatment. The conditions of the activation treatment are shown in Table 1.

[0040] Table 1 Catalyst activation conditions

[0041]

[0042] After the activation treatment, the raw material cyclohexanol was introduced into a fixed bed reactor for dehydrogenation reaction to prepare cyclohexanone. The reaction conditions were changed and the activity evaluation was carried out under the following reaction conditions. The results are shown in Table 2:

[0043] Reaction conditions (1) are: the liquid space velocity of the raw material cyclohexanol is 0.7h -1 , the reaction temperature is 240°C, and the reaction pressure is 0.3MPa;

[0044] Reaction conditions (2) are: the liquid space velocity of the raw material cyclohexanol is 1.5h -1 , the reaction temperature is 280°C, and the reaction pressure is 0.1MPa;

[0045] Reaction conditions (3) are: the liquid space velocity of the raw material cyclohexanol is 1.8h -1 , the reaction temperature is 260°C and the reaction pressure is 0.2MPa.

[0046] Table 2 Evaluation results of cyclohexanol dehydrogenation catalyst

[0047]

[0048] It can be seen from Table 2 that the catalyst for dehydrogenating cyclohexanol to cyclohexanone prepared by the present method has very good catalytic performance.

Claims

1. A method for preparing cyclohexanone by dehydrogenating cyclohexanol, characterized in that: The catalyst was loaded into a fixed bed reactor and activated by introducing a mixture of hydrogen and nitrogen. The activation conditions were as follows: temperature of 240°C, time of 45h, and volume concentration of hydrogen in the mixture of 0.5%. After the activation, the raw material cyclohexanol was introduced into the fixed bed reactor for dehydrogenation to prepare cyclohexanone. The temperature of the dehydrogenation reaction was 260°C, the pressure was 0.2MPa, and the cyclohexanol space velocity was 1.8h -1 , the catalyst is specifically prepared by the following method: According to the molar ratio of copper, zinc, chromium and zirconium being 4.7:4.5:4.7:1, 5L of a mixed aqueous solution of copper nitrate, zinc nitrate, chromium nitrate and zirconium nitrate with a mass percentage concentration of 30% was prepared; 1mol / L of potassium carbonate aqueous solution was added to the mixed aqueous solution at a stirring speed of 200rpm and 60°C to react, and the amount of potassium carbonate aqueous solution was controlled so that copper ions, zinc ions, chromium ions and zirconium ions were all precipitated. After reacting for 2h, the mixture was allowed to stand for stratification, and the supernatant was analyzed, and no Metal ions, the reaction solution is filtered and washed to obtain a precipitate; the obtained precipitate is dried at 120°C for 8 hours; then calcined at 450°C for 10 hours to obtain a calcined product, based on the mass of the prepared calcined product, the mass content of CuO is 30.7%, the mass content of ZnO is 29.7%, the mass content of Cr2O3 is 29.5%, and the mass content of ZrO2 is 10.1%; finally, 0.15% of the mass of the calcined product is added to the calcined product to form a graphite sheet, and the calcined product is obtained. Cylindrical catalyst.

Citation Information

Patent Citations

  • Dehydrogenation catalyst, preparation method and application thereof, and method for preparing cyclohexanone by cyclohexanol dehydrogenation

    CN103285847A

  • Catalyzer for dehydrogenation cyclohexanone to prepare cyclohexanol and application of catalyzer

    CN103861626A

  • Medium-temperature cyclohexanol dehydrogenation catalyst, preparation method and application thereof

    CN112387288A

  • Catalyst for preparing cyclohexanone by virtue of cyclohexanol dehydrogenation as well as preparation method thereof

    CN102247854A